Effect of beating process to soda anthraquinone pulp of oil palm male flower spikes fibre - Masrol, S.R.; Ibrahim, M.H.I.; Adnan, S.; Amir Shah, M.S.S.; Main, N.M.; Esa, M.F.; Othman, M.H. (Trans Tech Publications, 2015)
This study was carried out to investigate the effect of beating process to the characteristics of pulp and paper produced from oil palm oil male flower spikes (OPMFS). OPMFS pulp was prepared according to chemical Soda-AQ pulping process. 60 gsm handsheet of oil palm male flower spikes paper were prepared from OPMFS pulp with four different beating times which are O revolution, 1000 revolutions, 2000 revolutions and 3000 revolutions. All physical and mechanical characteristics were investigated according to T APPi and MS ISO standards. The results show that overall physical and mechanical characteristics of POMPS paper were influenced and enhanced by beating process between O until 3000 revolutions. This research demonstrate some potential characteristics of palm oil male flower spikes (OPMFS) paper to be investigated as a newly explored non-wood based raw material for papermaking raw material for papermaking.